Islamic Counseling Approach to Improve Adolescent Mental Health - Dede Rosyada; Syahrullah Syahrullah; Nahuda Nahuda; Dina Rahma Fadllilah; Irna Hasanah (Indonesian Journal of Islam and Public Health, 2022)
Mental health is an inner condition that is always in a calm, safe and peaceful state, and efforts to find inner peace can be made, among others, through self-adjustment by resignation (complete surrender to God). In this study, the researcher used references that refer to the discussion of Islamic counseling and adolescent health from 14 previous journals and one book with a range of 2010-2021 to conduct a series of studies. This research literature review concluded that Islamic counseling guidelines improve adolescents' mental health. The physical presence of the Qur'an brings blessings to people who believe in it. If a person faces life's difficulties and mental turmoil, such as stress, depression, or syndrome, it will be healed by the spiritual "magic" power in certain verses with the holy power of the transcendent realm. Human life is not just physical life.